Kaschub, M., y Smith, J. (2016). "Experiencing Music Composition in Grades 3-5" - Hernández, Ana Martínez (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2017)
This review explains how the book Experiencing Music Composition in Grades 3-5 is a guide for those teachers who want to start introducing music composition in a meaningful and significant way.